Rgg-LIKE TRANSCRIPTIONAL REGULATORS IN STREPTOCOCCUS spp. - A. V. Dmitriev (Sankt-Peterburg : NIIÈM imeni Pastera, 2016)
An ability of pathogenic bacteria to survive in different ecological niches, to successfully adapt to changing environments, to colonize different organs and tissues, and to cause numerous diseases in human and animals including severe invasive diseases is provided, in particular, by the presence of specific proteins involved in regulation of gene transcription. This review summarizes the current data on the Rgg-family (TIGR01716 family, The Institute for Genomic Research, http://www.jcvi.org) of regulatory proteins encoded by some of the low G+C gram positive bacteria such as Streptococcus gordonii, Streptococcus agalactiae, Streptococcus pneumoniae, Streptococcus mutans, Streptococcus thermophilus, Streptococcus suis and Streptococcus pyogenes. Proteins of this family has helix-turn-helix (HTH) motif at N-terminus which is able to bind promoter regions of the genes and regulate their transcription. The mechanisms of Rgg-dependent transcriptional regulation and the role of certain amino acids for functioning of Rgg-like proteins are discussed. The Rgg-like regulators have evolved to regulate diverse set of genes associated with virulence, metabolism, stress response, competence, biofilm formation, etc. The Rgg-like regulators are also involved in quorum sensing. Rgg-like proteins regulate not only the genes located adjacently to rgg, but also distantly located genes. Rgg-like proteins of different bacterial species have certain sequence similarity, and it is suggested that their genes are horizontally acquired. Rgg-dependent transcriptional regulation varies in a strainand species-specific manner that supports the hypothesis of the complexity of transcriptional regulation in gram-positive bacteria. The current review also discusses the role or Rgg-like regulators in control of virulent properties of gram-positive bacteria and their interaction with human host. Given the importance of Rgg-like regulators for virulence, these proteins (their genes or transcripts) can be considered as targets for development of the novel selective agents against different bacterial infections.